Rancang Bangun Sistem Monitoring dan Klasifikasi Lingkungan Hidup Larva Lalat Tentara Hitam (Hermetia Illucens) dengan Metode K-Nearest Neighbor (K-NN) - Amri Yahya; Rizal Maulana; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The process of biodegradation is the activity of using a microorganism to carry out the process of handling waste quickly. Microorganisms that can handle waste efficiently are black larvae. Environmental quality of larvae supports the process of biodiversity. The environmental quality monitoring system uses several sensors and a microcontroller which is packaged in the form of a monitoring and classification system. Classification of the k-NN method produces three classes namely